Origins of rolling friction. (29th June 2017) - Cross, Rod
Abstract: When a hard object rolls on a soft surface, or vice versa, rolling friction arises from deformation of the soft object or the soft surface. The friction force can be described in terms of an offset in the normal reaction force or in terms of energy loss arising from the deformation. The origin of the friction force itself is not entirely clear. It is investigated qualitatively in this paper by rolling a steel ball on soft foam and by rolling a foam cylinder on a hard surface. The deformation of the foam was observed visually, providing simple insights into the origin of the friction force.